Genetic analysis of nucleotide sequences of neuraminidase gene of highly pathogenic avian influenza A/H5N8 virus isolates recovered in the Russian Federation in 2020 - P. B. Akshalova; N. G. Zinyakov; A. V. Andriyasov; P. D. Zhestkov; Z. B. Nikonova; S. N. Kolosov; I. A. Chvala (Ветеринария сегодня)
Avian influenza is a highly dangerous viral disease that causes huge economic damage to poultry farming. Currently, highly virulent influenza virus with N8 neur- aminidase subtype is quite often detected in populations of domestic and wild birds in various countries of the world. The article provides data on complete nucleotide sequences of the neuraminidase gene of highly pathogenic avian influenza virus isolates recovered in the second half of 2020 from pathological material received from four regions of the Russian Federation. The conducted research showed that the subtype of the isolated virus was N8. According to the phylogenetic analysis, isolates of N8 virus belong to group 8C.4. During the phylogenetic analysis of the neuraminidase, we also took into account data on hemagglutinin classification, according to which H5N8 virus isolates belong to a widespread clade 2.3.4.4. Viruses of the clade were first registered in 2010 in China and they have been circulating up to now. The paper also provides data of a comparative analysis of nucleotide sequences of the studied isolates and the isolates from the international GenBank and GISAID databases, recovered in other countries from 2007 to 2020. During the analysis of the amino acid sequence of the studied isolates, no substitutions were found in the positions that affect resistance to neuraminidase inhibitors. The complete nucleotide sequences of the neuraminidase gene of the avian influenza virus subtype N8 (isolates A/domestic goose/OMSK/1521-1/2020, A/duck/Chelyabinsk/1207-1/2020, A/duck/Saratov/1578-2/2020, A/goose/Tatarstan/1730-2/2020) are published in the international GenBank and GISAID databases. Based on the analysis of the nucleotide sequences of the studied isolates, the article shows gradual evolution of the N8 subtype virus.